Clinical profiles and mortality risk factors in pediatric pulmonary hemorrhage: a single-center study in Saudi Arabia - Moath K. Alabdulsalam; Robayeh A. Asiry; Raghad T. Alhuthil; Abdulaziz S. Almusallam; Nora K. Alhelali; Tareq M. Alayed; Fahad B. Aljofan; Fawaz A. Alanzi; Tariq O. Alofisan; Abdullah T. Alturkia (Annals of Saudi Medicine)
BACKGROUND: Pulmonary hemorrhage (PH) is a rare, life-threatening event characterized by bleeding into the airways and lung parenchyma. OBJECTIVES: To explore the clinical characteristics of PH patients and investigate mortality-related risk factors, providing a holistic understanding of patient outcomes in this population. DESIGN: A retrospective cohort study SETTINGS: The Pediatric Intensive Care Unit (PICU) at King Faisal Specialist Hospital and Research Centre (KFSHRC), Riyadh, Saudi Arabia. PATIENTS AND METHODS: Pediatric patients with PH episodes (aged 1 month to 14 years) who were admitted from January 2014 to September 2019. MAIN OUTCOMES MEASURES: Clinical characteristics, outcomes, and mortality-related risk factors SAMPLE SIZE: 80 children RESULTS: The cohort had a sex ratio of 1:1 and a median age of 24 months [interquartile range: 9–78]. Medical histories included bone marrow transplant (51.3%), oncology cases (40.0%), chemotherapy (61.3%), chest infection (86.3%), and immunosuppressant use (71.3%). Additionally, most patients (87.5%) had acute respiratory distress syndrome during the PH episode. The overall PICU mortality rate was 82.5% (66/80), and was associated with thrombocytopenia, sepsis, renal impairment, liver dysfunction, multiorgan dysfunction, and altered code status in univariable analysis (all P <.05). Multivariate analysis identified sepsis, multiorgan dysfunction, and altered code status as key predictors of PICU mortality (P <.05). CONCLUSION: The high mortality rate reported emphasizes the need for tailored interventions and heightened vigilance, particularly in immunocompromised children. Future research will expand on these findings to refine current management protocols and further improve patient care in pediatric PH. LIMITATIONS: Retrospective study, single-center